Trust and Trust-Making in Africa's Global Connections - Kaag, Mayke,; Tarrósy, István,; Thiel, Alena, (Africa-Europe Group for Interdisciplinary Studies ;, 2025)
Trust and Trust-Making in Africa's Global Connections is a thought-provoking book contributing to both African Studies and the study of trust in society. The volume provides rich ethnographic insights into the ways trust and trust-making shape Africans' global encounters. It traces empirical foundations of trust and distrust, illustrates the wide variation in manifestations of trust-building, and critically positions these observations in the contemporary moment of global polycrisis. Trust and trust-making, we show, as these critically engage with global power relations, are acting both as a catalyst of harm and a potential source of positive change. Contributors: Mayke Kaag, Alena Thiel, István Tarrósy, Melina Kalfelis, Mark Kwaku Mensah Obeng, Geraldine Asiwome Ampah, Wiebe Nauta, Abdourahmane Seck.